A study on the Socio-Economic Status and level of Cognitive, Psychomotor and Affective Domains of Sidi Tribes in Open Sea Cage Culture - P.S. Swathilekshmi, R. Narayanakumar; C. Ramachandran (Indian Journal of Extension Education, 2018)
A study on the level of socio-economic conditions of communities/beneficiaries provides the base to formulate development plans and undertake corrective action for the posterity. The present study deals with the sociopersonal, socio-psychological and socio-economic characteristics of Sidis a primitive tribal group who are the beneficiaries of the ambitious cage culture programme of CMFRI under the Tribal Sub-Plan. A sample of 135 Sidi tribals consisting of 45 numbers of Sidis practicing cage culture, 45 numbers of non-practicing beneficiaries of the tribal society and 45 numbers of Sidis who were non practicing and non-beneficiaries of society were selected using multistage random sampling method. The findings of the study revealed that majority of the participant beneficiaries (58.33 percent) were having high school level of education, when compared to non-participant beneficiaries majority of whom were illiterates (55.55 percent). It could be inferred that, the participant beneficiaries had a higher average monthly income ie ` 1516.25 when compared to non-participant beneficiaries who earned an average monthly income of ` 854.25. Majority of the participant beneficiaries (41.67 per cent) had medium level of knowledge in cage culture followed by (50.00 per cent) who had medium level of attitude followed by 75 per cent had medium level of perceived skill towards cage culture.